Knowledge and practice of footcare among people with type 2 diabetes mellitus in Hospital Univeriti Sains Malaysia - Anak Uning, Elenser (PPSP, Universiti Sains Malaysia, 2007)
Diabetes may result in many other health conditions but the most common outcome of diabetes is complications associated with the foot. Unfortunately, diabetic foot tends to be underrecognised as a health issue, despite the fact that ulceration, gangrene and amputations are more common complication of diabetes. The most basic measure in preventing the diabetic complications would be self management of foot care. Objectives: The aim of the study is to determine the knowledge about foot care and its practice among people with type 2 diabetes mellitus in HUSM. Methodology: This study was a cross-sectional design and descriptive study. Seventy Type 2 DM patients who were attending to HUSM selected wards and Diabetes Center were recruited in this study. Each respondent was given a self-administered questionnaire. From this questionnaire, the knowledge score and practice of foot care were calculated and analyzed using Statistical Package for Social Science version 11.0 (SPSS). Deficiency in foot care knowledge and practices that increase the risks of diabetic foot were identified. Results: The mean knowledge score was 6.53 (S.D. 1.99) out of possible 10. There was a significant relationship between sex and knowledge score, in which man had higher knowledge score compared to female. Other sociodemographic factors have no significant relationships. Deficiency in knowledge includes the inadequate knowledge of frequency to inspect foot, inability to check the water temperature before washing feet and inability to check footwear before wearing it. Practices that put patients at high risks include did not inspect foot daily, always wear slipper and failed to check temperature of the water before wash feet. Conclusion: This study revealed that the level of foot care knowledge is moderate among people with type 2 DM in HUSM. The practice of foot care is also found unexpectedly low among the DM patients. This study also has highlighted some areas of foot care knowledge and practice that are deficient. Those aspects of foot care knowledge which are low needs improvement and those undesirable practices that put patients at risk of developing foot problems should be changed and replace with good foot care practice.